Nd isotopes from Yerba Loca Formation (Upper Ordovician), Cuyania terrane, Argentina - Abre, P. (2006)
Several arguments as well as geochemical data from the basement rocks support the allochthonous models of the Precordillera (Cuyania) Terrane as derived from Laurentia (e.g. Ramos et al., 1986; Dalla Salda et al., 1992; Astini et al., 1995). Less certain are the time and type of collision with Gondwana. However, other authors have proposed a parautochthonous evolution based on biostratigraphical and structural data, displaced during Ordovician–Devonian times (e.g., Aceñolaza et al., 2002; Finney et al., 2005). To contribute to the discussion about tectonic models for the Precordillera, preliminary Nd isotope data from an ongoing provenance study on the Caradocian rocks from the Yerba Loca Formation are here presented.